PENGARUH KUANTITAS GARAM TERHADAP KUALITAS BEKASAM - zainal burlian; Syarifah Syarifah; Imamul Huda (Biota, 2016)
Fish is one of the animal protein sources consumed by people because it is relatively easy to obtain and affordable. The abundant of the fish needs some ways to preserve it, one of them is by making bekasam. Bekasam is fish fermented product which is procesed with the addition of rice and salt. One of the function of the salt is to select microorganisms that produce proteolytic enzymes.The purpose ofthis study was to know influance of different salt concentrations to ward the quality of fish bekasam.The research was conducted in August 2015 in Chemistry Laboratory of Biology Education Study Program, Teaching Training and Tarbiyah Faculty UIN Raden Fatah Palembang. The research method was an experimental laboratoryusing a CRD with 4 treatments and 3 replication. The treatments were salt concentrationK0 (10% b/v), K1 (20% b/v), K2 (30% b/v) and K3 (40% b/v). The test parameters observed were theacidity and hedonic test (color, smell and taste). The parametric data for the acidity was analyzed by ANOVA test, while nonparametric data(hedonic) used the organoleptic test. The results showed that based on ANOVA, the different salt concentration gave a very significant different influance (P=0,01) toward the acidity value, that Fcount> Ftable is 26,16 > 7,59. Based on research result, the acidity of each K0, K1, K2and K3 was 1,13 N, 1,00 N, 1,02 Nand  0,42N.Treatment of 10% salt concentration resulted the highest  acidity 1,13 N.While from hedonic test showed that bekasam with 20%salt concentration was the most preferred